Copper-boxmi complexes as highly enantioselective catalysts for electrophilic trifluoromethylthiolations - Deng, Qing-Hai; Rettenmeier, Christoph Alexander; Wadepohl, Hubert; Gade, Lutz H. (Chemistry - a European journal, 2014)
The enantioselective trifluoromethylthiolation of β-ketoesters using chiral copper-boxmi complexes as catalysts is reported. A number of α-SCF3-substituted β-ketoesters have been obtained with up to >99 % enantiomeric excess (ee), and the trifluoromethylthiolated products were then transformed diastereoselectively to α-SCF3-β-hydroxyesters with two adjacent quaternary stereocenters.
Published online on December 11, 2013
Gesehen am 15.10.2020